Free radical competitions in polylactide/bio-based thermoplastic polyurethane/ free radical initiator ternary blends and their final properties. (1st May 2015) - Zhang, Lisheng; Xiong, Zhu; Shams, S. Saqib; Yu, Ruilei; Huang, Juncheng; Zhang, Ruoyu; Zhu, Jin
Abstract: The reactive blending system of free radical initiator (L101), polylactide (PLLA) and bio-based polyurethane (Bio-TPU) elastomer containing double bonds was investigated. There existed a competition for free radicals between the PLLA and Bio-TPU, because free radicals could attack both the tertiary hydrogen in PLLA chains and the double bonds in Bio-TPU. The behavior of competition for free radicals between PLLA and toughening phase was pointed out and analyzed in this work for the first time. Observations from all kinds of characterization lead us to believe that the double bonds in Bio-TPU were more prone to react with free radicals. The competition for free radicals played an important role on the interfacial properties of the blending systems, and consequently, on the thermal and mechanical properties of the blends. In PLLA/Bio-TPU/L101 (90/10/0.1, 90/10/0.3) blends, excellent ductility and high tensile strength were found at the same time owing to largely improved compatibility and much higher crystallinity. The elongation at break of these two samples were improved 36 and 34 times compared to pure PLLA separately, accompanied with only 16% and 18% decrease of the tensile strength. This work may be helpful for better understanding of similar reactive blending systems and designing PLLA blends with comprehensive properties. Graphical abstract: Highlights: Reactive blending system of PLLA/Bio-TPU/free radical initiator was researched in this work. The double bonds in Bio-TPU were more prone to react with free radicals. The ternary blends show excellent ductility and high tensile strength at the same time.